Notification methods in wireless systems - Nawrocki, Piotr; Jakubowski, Mikołaj; Godzik, Tomasz (Wydawnictwa AGH, 2016)
Recently, there has been an increasing need for secure, efficient, and simple notification methods for wireless systems. Such systems are meant to provide users with precise tools best suited for work or leisure environments, and a lot of effort has been put into creating a multitude of applications. At the same time, however, not much research has been made into determining which of the available protocols are best suited for each individual task. A number of basic notification methods are presented here, and tests have been performed for the most-promising ones. An attempt has been made to determine which of the methods have the best throughput, latency, security, and other characteristics. A comprehensive comparison is provided, which can be used to select the right method for each individual project. Finally, conclusions are provided, and the results from all of the tests conducted are discussed.
Computer Science
Bibliogr. s. 538-539.
Keywords: notification methods; wireless systems; energy consumption